Effectiveness of Using Wood Powder and Litter Fertiliser on Rice Paddy Farming (Implementation in Tanjung Harapan Farmer Group, Setiris Village, Maro Sebo District, Muaro Jambi Regency) - Ulma, Riri Oktari; Damayanti, Yusma; Nurchaini, Dewi Sri; Yulismi, Yulismi; Mukhlis, Mukhlis (Pascasarjana Universitas Mataram, 2024)
The use of wood powder and leaf litter fertilizer in wetland rice farming has proven to be effective in improving agricultural productivity sustainably. The research was conducted in Setiris Village, particularly in the Tanjung Harapan Farmer Group, in Jambi Province. This organic fertilizer, besides reducing the environmental damage caused by wood powder waste, has also brought about positive changes in farming practices. Training and counseling have been conducted to enhance farmers' understanding of using organic fertilizer. Wood powder and leaf litter fertilizers enhance crop productivity and quality, improve soil structure, and reduce production costs. Thus, the use of these fertilizers supports sustainable and environmentally friendly farming in Setiris Village.